The significant factors influencing landscape satisfaction among residents towards home garden landscape in Puchong, Selangor / Siti Nor Nadrah Muhamad ... [et al.] - Muhamad, Siti Nor Nadrah; Abd Razak, Nur Illani; Norman, Nur Afiqah; Muhammat Pazil, Nur Syuhada; Wan Shahidan, Wan Nurshazelin; Mohamad Nor, Nor Azriani (Universiti Teknologi MARA, Perlis, 2022)
Landscape satisfaction towards home garden landscape is vital to preserving home garden ownership. This study was conducted to determine the factors influencing landscape satisfaction towards home garden landscape as there is an insufficient number of studies regarding the subject. This study also focused on residents who own a home garden and mainly live in a residential area in Puchong, Selangor, as the respondents. Quantitative data through a survey questionnaire was collected among them. The Snowball sampling technique was used as the sampling technique. SPSS software was deployed to conduct frequency analysis, reliability analysis, correlation analysis, and regression analysis for the data analysis. The research study found that plant diversity was most significant to landscape satisfaction since the p-value of plant diversity was 0.000 and followed by the environmental awareness factor with a p-value of 0.011. It can be concluded that plant diversity and environmental awareness were influential variables in the landscape satisfaction toward the home garden landscape. The independent variable could be varied to explore other factors influencing the landscape satisfaction towards home garden landscape in Puchong, Selangor, for future research.